Current approaches in biomaterial-based hematopoietic stem cell niches. (May 2018) - Bello, Alvin Bacero; Park, Hansoo; Lee, Soo-Hong
Graphical abstract: On making an in vitro bone marrow (BM): The essential components. To make a bone marrow mimicking microenvironment for the growth and expansion of hematopoietic stem cells, several factors need to be taken into consideration. These factors include the BM's in-vivo biochemical properties (growth factors hormones, co-existing cells, ECM, gas concentrations, regulated gene expression) and the biomaterial properties (type, dimension, topography, and mechanical strength). Abstract: Hematopoietic stem cells (HSCs) are multipotent progenitor cells that can differentiate and replenish blood and immune cells. While there is a growing demand for autologous and allogeneic HSC transplantation owing to the increasing incidence of hereditary and hematologic diseases, the low population of HSCs in cord-blood and bone marrow (the main source of HSCs) hinders their medical applicability. Several cytokine and growth factor-based methods have been developed to expand the HSCs in vitro ; however, the expansion rate is low, or the expanded cells fail to survive upon engraftment. This is at least in part because the overly simplistic polystyrene culture substrates fail to fully replicate the microenvironments or niches where these stem cells live. Bone marrow niches are multi-dimensional, complex systems that involve both biochemical (cells, growth factors, and cytokines) and physiochemical (stiffness, O2 concentration, and extracellular matrix presentation) factors that regulate the quiescence, proliferation, activation, and differentiation of the HSCs. Although several studies have been conducted on in vitro HSC expansion via 2D and 3D biomaterial-based platforms, additional work is required to engineer an effective biomaterial platform that mimics bone marrow niches. In this study, the factors that regulate the HSC in vivo were explained and their applications in the engineering of a bone marrow biomaterial-based platform were discussed. In addition, current approaches, challenges, and the future direction of a biomaterial-based culture and expansion of the HSC were examined. Statement of Significance: Hematopoietic stem cells (HSC) are multipotent cells that can differentiate and replace the blood and immune cells of the body. However, in vivo, there is a low population of these cells, and thus their use in biotherapeutic and medical applications is limited (i.e., bone marrow transplantation). In this review, the biochemical factors (growth factors, cytokines, co-existing cells, ECM, gas concentrations, and differential gene expression) that may regulate the over-all fate of HSC, in vivo, were summarized and discussed. Moreover, different conventional and recent biomaterial platforms were reviewed, and their potential in generating a biomaterial-based, BM niche-mimicking platform for the efficient growth and expansion of clinically relevant HSCs in-vitro, was discussed.